Modernity and Malaysia settling the Menraq forest nomads - Gomes, Alberto G., 1954- (Modern anthropology of South-East Asia., 2007)
Bringing together the results of over twenty-five years of research on the indigenous peoples of Malaysia, this fascinating book illustrates the experiences of modernity in indigenous communities through a detailed case study of the Rual Menraq of Malaysia.